2015
DOI: 10.4172/2155-6148.1000503
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Midazolam in the Prevention of Etomidate Induced Myoclonus

Abstract: Introduction: Etomidate, the imidazole derivative, is an intravenous anaesthetic induction agent, having stable hemodynamic profile, minimal respiratory side effects and histamine release. It is extremely useful in hemodynamically compromised patients. But the most common problem associated with its induction is myoclonus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…It was shown that myoclonus occurred at a significantly lower rate in patients who received a bolus pre-treatment dose followed by a therapeutic dose (11). Also, Salim et al showed that the intensity of myoclonus was higher in patients not receiving pre-treatment than in the other two groups but no significant difference was observed between the two groups receiving etomidate pre-treatment (20). In our study, we tried an initial bolus dose of pre-treatment, but did not study the bolus and infusion administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that myoclonus occurred at a significantly lower rate in patients who received a bolus pre-treatment dose followed by a therapeutic dose (11). Also, Salim et al showed that the intensity of myoclonus was higher in patients not receiving pre-treatment than in the other two groups but no significant difference was observed between the two groups receiving etomidate pre-treatment (20). In our study, we tried an initial bolus dose of pre-treatment, but did not study the bolus and infusion administration of the drug.…”
Section: Discussionmentioning
confidence: 99%